2021
DOI: 10.1038/s41598-021-96066-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of RT-PCR, RT-nested PCRs, and real-time PCR for diagnosis of severe fever with thrombocytopenia syndrome: a prospective study

Abstract: We designed a highly sensitive reverse transcription nested polymerase chain reaction targeting the M-segment (NPCR-M) of severe fever with thrombocytopenia syndrome (SFTS) virus. NPCR-M was performed in parallel with three other referenced PCR assays QPCR-S, PCR-M, and NPCR-S to assess their clinical usefulness as routine diagnostic techniques for SFTS. In this multi-centered prospective study, 122 blood samples from 38 laboratory-confirmed SFTS patients and 85 control samples were used. The results demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…However, currently, conventional RT-PCR, nested RT-PCR, and real-time RT-PCR are used for the detection of SFTS. 19 In our study, we found heterogeneity in RT-PCR caused by threshold effects. This may be because of the different cycle threshold (Ct) values used as criteria for determining positivity in the studies analyzed.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…However, currently, conventional RT-PCR, nested RT-PCR, and real-time RT-PCR are used for the detection of SFTS. 19 In our study, we found heterogeneity in RT-PCR caused by threshold effects. This may be because of the different cycle threshold (Ct) values used as criteria for determining positivity in the studies analyzed.…”
Section: Discussionmentioning
confidence: 50%
“…Additionally, researchers can also develop new and more effective primers/probes for PCR research and develop more precise commercial kits for the diagnosis of SFTS. However, currently, conventional RT‐PCR, nested RT‐PCR, and real‐time RT‐PCR are used for the detection of SFTS 19 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations